Doing justice, preventing crime - Tonry, Michael H. (New York, NY : Oxford University Press, 2020)
'Doing Justice, Preventing Crime' lays normative and empirical foundations for building new, more just, and more effective systems of sentencing and punishment in the 21st century. The overriding goals are to prevent crime while treating people convicted of crimes justly, fairly, and even-handedly; to take sympathetic account of the circumstances of peoples' lives; and to punish no one more severely than he or she deserves. Michael Tonry discusses philosophy and punishment theory, surveys what is known about the deterrent, incapacitative, and rehabilitative effects of punishment, and explains what needs to be done to move from an ignoble present to a better future.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 23, 2020).
Keywords: Criminal justice, Administration of -- United States; Sentences (Criminal procedure) -- United States; Crime prevention -- United States; True Crime; Social services & welfare, criminology